Prdx6 Deficiency Ameliorates DSS Colitis: Relevance of Compensatory Antioxidant Mechanisms. (12th February 2017) - Melhem, Hassan; Spalinger, Marianne R.; Cosin-Roger, Jesus; Atrott, Kirstin; Lang, Silvia; Wojtal, Kacper A.; Vavricka, Stephan R.; Rogler, Gerhard; Frey-Wagner, Isabelle
Abstract: Background and Aims: An imbalance between cellular antioxidant defence system[s] and reactive oxygen species [ROS]-driven oxidative stress has been implicated in the pathogenesis of inflammatory bowel disease. Peroxiredoxin [PRDX] 6 contributes to an appropriate redox balance by clearing ROS and reducing peroxidized membrane phospholipids. We here studied the role of PRDX6 in acute and chronic dextran sodium sulphate [DSS]-induced colitis. Methods: To investigate the impact of PRDX6 on intestinal inflammation, we used wild type [WT], Prdx6 knock-out mice [ Prdx6 -/ - ] and transgenic mice [ Prdx6 tg/tg ], overexpressing Prdx6 . Acute and chronic colitis was induced by DSS in WT, Prdx6 -/ - and Prdx6 tg/tg mice. Colitis was evaluated by endoscopy, colon length, histopathological assessment and myeloperoxidase [MPO] activity. Changes in mRNA and protein expression of pro-inflammatory cytokines and antioxidant enzymes were evaluated by real-time quantitative polymerase chain reaction [RT-qPCR] and western blot. Total glutathione [GSH] levels in colon samples were determined. Results: Prdx6 -/ - mice exposed to acute and chronic DSS showed a significant decrease in the clinical parameters and in colonic expression of pro-inflammatory cytokines compared with WT mice. mRNA expression of antioxidant enzymes in colon samples was significantly increased in Prdx6 -/ - compared with WT mice exposed to acute and chronic DSS. In addition, total GSH levels were increased in Prdx6 -/ - mice treated with DSS in comparison with WT. Overexpression of Prdx6 did not significantly influence acute and chronic colitis. Conclusions: Our data indicate that a lack of the antioxidant enzyme PRDX6 protects against the development of acute and chronic experimental colitis and is associated with increased expression and function of other antioxidant enzymes, suggesting effective compensatory mechanisms.